Evaluation of the effectiveness of basic schools in the Rosaifa Directorate of Education in Zarqa Governorate According to some educational quality standards from the point of view of principals and teacher - Al-Anani, Abeer AbdAlkareem (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the effective school evaluation related to the quality of education and its availability in basic schools as seen by principals and teachers. It reached (150) principals and teachers; From the Rusaifa/Zarqa Directorate of Education, 56 of whom are principals, 94 are teachers, and the results showed that the availability of effective school characteristics related to the quality of education in basic schools as seen by principals and teachers obtained an overall average (3.43 out of 5) with a (large) availability and at the level of fields; The school’s vision and the quality of its mission got the highest average (3.60Then educational leadership and supervision with an average of (3.44), both with a degree of availability (large), and the third was the educational climate of the school with an average of (3.36) and finally the educational process with an average of (3.32), both with a degree of availability (medium), and the study sample consisted of 92 principals and 1200 teachers using tools prepared To this end, it also showed that there were no statistically significant differences at the level (α ≥ 0.05) between the views of the sample according to the variables (gender, years of experience, educational qualification and type of school). Activating the role of the school principal, and raising the ceiling of interest in values and trends in the educational process. The study also proposes to investigate the relationship between school climate and effective school and to analyze administrative patterns in basic schools.